Determinants of the Evolution of Physical Culture in the Koszalin Region in 1945−1950 - Agnieszka Połaniecka; Anna Błaszkowska (Lesya Ukrainka Volyn National University, 2019)
In the first post-war years, in the Koszalin region there was a multi-million migration related to the settlement of the so-called Recovered Territories. Rapid development and settlement of the largest number of Poles in the area became one of the most important tasks after the end of hostilities. It should be noted that the population that came to the so-called The Recovered Territories, built from scratch, living conditions and certain areas of social life, including cultural and sporting life. Among the settlers who arrived in Koszalin, there were pre-war sports activists, players, members of associations and clubs who, apart from professional activities, took up the organization of sport. In a new, uneasy situation, Poles' environments organized their cultural and sporting lives without closing to the emerging and mixed communities. The first organizational units of physical culture in Central Pomerania were sports clubs, which primarily formed at selected professional groups, the most active were groups of railwaymen, militiamen and craftsmen. Sport in this area was more than just competition or "fun for the body and soul", it also served to integrate the settled population. This applied not only to rivals competing with each other, but also fans watching sporting events, which became a way of spending time and an opportunity to celebrate together. Not only, however, they also influenced the formation of social bonds. Cooperative works for the development of sport formed the foundation of a new social life.